2003
DOI: 10.1007/s00468-002-0221-3
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical and ultrastructural studies on Salix alba and S. matsudana seeds

Abstract: Mature seeds of Salix alba L. and Salix matsudana Koidz. are exendospermous and consist of an embryo and a seed coat. Ultrastructural studies show the presence of protein bodies, lipid bodies, chloroplasts, and a nucleus in the cells of most of the embryo tissues. Protein bodies always contain two or more globoid crystals. Energy-dispersive X-ray analysis of globoid crystals revealed the presence of P, K, Mg and Ca as the main constituents in all tissues. The chloroplasts present well-developed grana and, freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Additionally, the scattered distribution of tocotrienols within the plant kingdom is not yet completely understood ( Falk and Munné-Bosch, 2010 ). Together with tocochromanols and carotenoids, Chl can also sometimes be present in seeds, mostly as a remnant of incomplete degradation during seed maturation but also as part of a fully operative photosynthetic apparatus in a couple of species in which mature seeds are photosynthetic ( Maroder et al, 2003 ). From an anthropocentric perspective, the presence of Chl in seeds is usually considered a negative aspect due to reduced seed storability [as is the case of photosynthetic seeds from Salix ( Roqueiro et al, 2010 )] and decreased marketability of seed crops [e.g., for soybean seeds with incomplete degradation of Chls ( Teixeira et al, 2016 )].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the scattered distribution of tocotrienols within the plant kingdom is not yet completely understood ( Falk and Munné-Bosch, 2010 ). Together with tocochromanols and carotenoids, Chl can also sometimes be present in seeds, mostly as a remnant of incomplete degradation during seed maturation but also as part of a fully operative photosynthetic apparatus in a couple of species in which mature seeds are photosynthetic ( Maroder et al, 2003 ). From an anthropocentric perspective, the presence of Chl in seeds is usually considered a negative aspect due to reduced seed storability [as is the case of photosynthetic seeds from Salix ( Roqueiro et al, 2010 )] and decreased marketability of seed crops [e.g., for soybean seeds with incomplete degradation of Chls ( Teixeira et al, 2016 )].…”
Section: Introductionmentioning
confidence: 99%
“…If the seeds fail to find a suitable place for germination, they would lose their germinative capacity within a few days (Chmelař, Meusel 1986). White willow is ranked in the group of species with an orthodoxically short viability of seeds also by Maroder et al (2003). Our experiments show that the seeds can keep a nearly 100% germinative capacity for 3 days that are followed by a rapid decrease.…”
Section: Case Study 2: the Regional Biocorridor Věstonice Developmentmentioning
confidence: 71%
“…In Salix spp seeds the chloroplasts with chlorophyll and thylakoid membranes are conserved in mature seeds (Maroder et al, 2003), which could lead to the production of free radicals (FRs) by auto-oxidation affecting phospholipids, glycoproteins and the relation between PUFAs and SFAs (Roqueiro et al, 2010 and. Some authors have reported that the auto-oxidation process generates FRs and ROS which produce damage to molecules, membranes and organelles (Priestley and Leopold, 1983;Priestley, 1986;Wilson and McDonald, 1986;Ponquett et al, 1992;Maroder et al, 2003;Roqueiro et al, 2010). In the dehydrated state, molecular defenses against FRs and ROS would be insufficient and/or scarcely efficient, and enzymatic defenses inactive (Nandi et al, 1997;Bailly, 2004).…”
Section: Vacuum Drying (Vd)mentioning
confidence: 99%